The Effect Of The Guided Inquiry Learning Model On Students’ Mathematical Communication Skills - Tahta Zulfa Sya'bana; Nurhanurawati; Santy Setiawati (Universitas Teknokrat Indonesia, 2026)
This quasi-experimental study aimed to analyze the effect of implementing the guided inquiry learning model on students’ mathematical communication skills. The research population consisted of all eighth-grade students of SMP Negeri 2 Sekampung Udik, East Lampung, in the 2025/2026 academic year, totaling 184 students. The sample of this study comprised students from classes VIII.3 and VIII.5, with 30 and 28 students respectively, selected using the cluster random sampling technique. The research design employed was a posttest-only control group design. The data analyzed were quantitative data on students’ mathematical communication skills obtained through an essay test on the topic of Systems of Linear Equations in Two Variables (SPLDV). Data analysis was conducted using a t-test. The results showed that students who learned using the guided inquiry learning model had higher mathematical communication skills than those who participated in conventional learning. Therefore, it can be concluded that the implementation of the guided inquiry learning model has a significant effect on students’ mathematical communication skills.